Journalism and thinking skills / Azman Azwan Azmawati - Azwan Azmawati, Azman (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2006)
The increasing complexity of issues that mass media covers and the challenge to present it in the most profound approach is indeed a demanding task. Recent developments - locally and internationally - are testimonies that journalists can no more simply hold on to the gift for words in order to come out with an effective reporting. In today s ever-challenging world, be it political, social, economics – a critical, analytical, creative and profound reporting is the order of the day. Today s world does not need a journalist who merely simply fits her/his notes into the existing newspaper category, which is hard news and feature. This simple non-intellectual kind of reporting is no longer acceptable by the readers. Readers want a broader and comprehensive outlook on news. Facts need to be dissected and presented in a critical and analytical manner. Therefore, a revolution in the journalism curriculum must take place if we want to see a more proactive reporting.